Fenomena Sandwich Generation dan Dampaknya terhadap Kesejahteraan Tenaga Kerja di Indonesia - Halimatus Sa'diyah; Sabrina Arsy Wijaya; Ana Sakinah; Nurus Sobakh (Indonesia Economic Journal, 2026)
The sandwich generation is a phenomenon in which productive-age individuals must bear the financial burden of two generations simultaneously, namely elderly parents and children who are still financially dependent. In Indonesia, this phenomenon is increasingly widespread due to the growing elderly population, rising cost of living, limited old-age security, and strong family cultural values that encourage cross-generational financial responsibility. This study aims to explain the concept of the sandwich generation, analyze its contributing factors, and examine its impact on the welfare of the workforce in Indonesia. The method used is a systematic literature review by examining various scientific sources including journals, books, research reports, and relevant official publications. The findings indicate that the sandwich generation phenomenon significantly affects workforce welfare, encompassing financial pressure, declining quality of life, difficulty in saving and investing, and reduced productivity due to work-related stress and emotional exhaustion. At the macro level, the low saving capacity of this group also reduces the flow of productive investment funds within the national economy. To address this condition, a synergy is needed between improving financial literacy at the individual and family level and strengthening social protection policies by the government, so that workforce welfare can be maintained and the cycle of cross-generational financial vulnerability can be minimized.